2004
DOI: 10.1017/s0012162204000519
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Function Classification System and outcome tools for assessing ambulatory cerebral palsy: a multicenter study

Abstract: The relationships between different levels of severity of ambulatory cerebral palsy, defined by the Gross Motor Function Classification System (GMFCS), and several pediatric outcome instruments were examined. Data from the Gross Motor Function Measure (GMFM), Pediatric Orthopaedic Data Collection Instrument (PODCI), temporal-spatial gait parameters, and oxygen cost were collected from six sites. The sample size for each assessment tool ranged from 226 to 1047 participants. There were significant differences am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 26 publications
4
59
0
1
Order By: Relevance
“…The comparison between the functional areas or domains is quite limited because each scale has a different number of items. Thus, to make this comparison possible, the net scores obtained in the PEDI were added and then converted to continuous scores according to the children's levels of disability (0-100) 1,9,17 .…”
Section: Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison between the functional areas or domains is quite limited because each scale has a different number of items. Thus, to make this comparison possible, the net scores obtained in the PEDI were added and then converted to continuous scores according to the children's levels of disability (0-100) 1,9,17 .…”
Section: Assessment Toolsmentioning
confidence: 99%
“…The heterogeneity of the health conditions of children with CP does not allow a classification of motor impairment levels, and it is also a challenge for multiprofessional rehabilitation teams to use measures based on children's functional performance. This occurs because several studies 5,[9][10][11][12][13][14] present the functional scenario of the severity levels of CP in daily activities but do not describe the impact of the isolated disorder or the disability during the performance of these tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal CP classification methods, such as the GMFCS, have been developed in order to standardize the clinical variability, which is one of the major characteristics of CP 3) . In addition, the GMFCS is now extensively used in developmental research and clinical practice 4) , and its relation with measures of gait 5) , energy efficacy 6) , participation restriction 7) , and healthrelated quality of life 8) in the population with CP has been explored. It has been noted that traditional classification systems describing CP type by limb distribution (hemiplegia, diplegia, and quadriplegia), albeit useful for clinical and epidemiological purposes, have limited value as indicators of mobility.…”
Section: Introductionmentioning
confidence: 99%
“…It is now used extensively in developmental research and clinical practice, 3 and its relation with measures of gait, 4,5 energy efficiency, 4,6 participation restriction, 7 and health-related quality of life [8][9][10] in the population with CP has been explored. Although increasing numbers of papers lend weight to the validity of the GMFCS, 1,4,11,12 very few papers have explored the reliability of the classification system. Palisano et al's landmark paper 1 demonstrated good interrater reliability (κ=0.75) between all five GMFCS levels in 40 children with CP aged 2 to 12 years.…”
mentioning
confidence: 99%